Fullwave theory of Δv/v SAW waveguide and couplers - GAFKA, D. (Archives of Acoustics, 1991)
This paper considers propagation of a surface acoustic wave (SAW) along a multiperiodic system of electrodes (note: a multiperiodic system is a system with a group of several equidistant electrodes with equal width occuring periodically with a certain period) distributed on the surface of a piezoelectric half-space. The boundary problem with homogeneous mechanical and mixed electric boundary conditions was solved on the basis of properties of the effective surface permittivity and Floquet's theorem for periodic structures. New functions satisfying adequate conditions in an assumed multiperiodic system were formulated. A dispersion relation for the velocity of a SAW guided along electrodes was derived. The presented theory was applied in numerical analysis of SAW velocity dispersion in a Δv/v single and two-electrode waveguide, assuming an adequately long repetition period of groups of electrodes. Velocities and field decay distributions for two modes – symmetric and asymmetric are given for a two-electrode waveguide. The coupling coefficient between both electrodes of a coupler constructed on the basis of such a waveguide was calculated.